UJI KEBERHASILAN PENETASAN TELUR BURUNG MALEO GUNUNG (Aepypodius arfakianus) MENGGUNAKAN PENETASAN BUATAN - Hotlan Hotlan Manik; Abadi Jading; Rawati Panjaitan (VOGELKOP: Jurnal Biologi, 2023)
Environmental problems are a crucial problem because they quickly destroy the changing natural ecological balance, especially for animals whose lives are very dependent on the season, their natural habitat, and the availability of food in nature, especially Wattledbrush-turkey. The uncontrolled use of eggs and meat by these birds accelerates the extinction of animals in their natural habitat. Outside captive habitats for utilization purposes require attention to conservation and human needs. One of the efforts to accelerate the population is through artificial reproduction. The aim of the research was to obtain a model/prototype that was in accordance with natural conditions by using hatchery quality parameters so that the hatchability of bird eggs was expected to be increased. Research using trial and error method with experimental techniques. The results of testing the performance of the tool can be concluded that the incubator can function optimally and is stable in temperature and humidity so that the quality and quantity of hatching can increase by up to 80%. Testing of hatchability and hatching quality continues to be carried out to improve the performance of incubators that are more economical and easy to operate so that captive breeding activities outside their habitat (ex-situ) for the conservation and cultivation of endemic Papuan birds can be carried out.